Coronally advanced flap with and without hyaluronic acid (HYALOSS) for the treatment of gingival recession - a randomized clinical trial - Saxena Apoorva; Bhusari Prashant; Singh Abhilasha; Nagi Ravleen; Chaturvedi Shailendra Singh (EDP Sciences, 2022)
Objectives: To compare and evaluate the surgical outcome of gingival recession treatment using CAF alone or in conjunction with hyaluronic acid (HA) on Miller's Class I and class II gingival recession defects. Materials and methods: After randomisation, the control group (15 patients) received CAF alone and the test group (15 patients) received HA as an adjunct to CAF technique for an isolated gingival recession accompanied by an adequate width of keratinized gingiva on maxillary canines and premolars. All patients were evaluated at 7, 15, 30, 60 and 90 days interval post-operatively. Data obtained was subjected to statistical analysis and p value <0.05 was considered as statistically significant. Results: At 90 days interval statistically highly significant root coverage was obtained with mean gain of 66.1% in control group and 86.6% in test group. Statistically significant reduction in depth of gingival recession and gain in clinical attachment level was found for control and the test groups, and intergroup comparison showed statistically significant differences for root coverage and clinical attachment level between the groups (p = 0.000), however no significant differences were found for width of attached gingiva, keratinized gingiva and gingival thickness between the groups at 90 days (p > 005). Conclusion: HA has proven to be beneficial in the field of regenerative therapy. Our analysis suggested that HA can be used as a promising adjunct with CAF for root coverage, however further studies are required to imply the results on larger population.